AN EXPERIMENT WITH THE CASE METHOD IN TEACHING FEDERAL INCOME TAXES. - Beckert, Ralph F.; van Horn, Lawrence (The Accounting Review, 1965)
Abstract The Division of Public Accounting offers instruction for students who desire a career in accounting and it is particularly oriented towards the public accounting profession in the United States. The students in the Division of Business Administration desire a broad, general business education and do not intend to make a career of accounting. The method of instruction and course content has proven very satisfactory for the public accounting students but quite inadequate for the business administration students. The public accounting students are anxious to learn how to solve specific, technical income tax problems and how to perform detailed tax computations and analyses. This kind of work will make up an important part of their assignments in the field of public accounting. All of the students in the Division of Public Accounting have studied many accounting subjects before enrolling in the federal income tax course. Of course, the study of federal income taxes comes much easier and more quickly for students who have a good accounting foundation than for those who do not.